1963
DOI: 10.1172/jci104750
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alterations of Plasma Sodium and Potassium Concentration on Aldosterone Secretion*

Abstract: Mlany studies have been conducted on the relation of electrolytes to the control of aldosterone secretion. It was reported by Luetscher and Axelrad (1) and confirmed by others (2-4) that a low Na intake augments the rate of urinary aldosterone excretion in normal man. Also, it has been clearly established that chronic Na depletion increases aldosterone secretion in sheep (5, 6), dogs (7,8), and rats (9). On the other hand, the relation of K intake to aldosterone production has never been settled. Several inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
2

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(54 citation statements)
references
References 28 publications
1
50
1
2
Order By: Relevance
“…The cells of the juxtaglomerular apparatus may function as osmoreceptors (Fisher et al, 1965). There is experimental evidence that aldosterone secretion is decreased when the plasma sodium concentration is raised experimentally (Coghlan et al, 1960;Davis et al, 1963), but no information appears to be available for man. Our patient may demonstrate the human counterpart of these experiments.…”
Section: Case Reportmentioning
confidence: 99%
“…The cells of the juxtaglomerular apparatus may function as osmoreceptors (Fisher et al, 1965). There is experimental evidence that aldosterone secretion is decreased when the plasma sodium concentration is raised experimentally (Coghlan et al, 1960;Davis et al, 1963), but no information appears to be available for man. Our patient may demonstrate the human counterpart of these experiments.…”
Section: Case Reportmentioning
confidence: 99%
“…Previous studies have shown that aldosterone production can be markedly influenced by changes in potassium ( [1][2][3][4][5]. It is still uncertain, however, whether the modulating effect of potassium is dependent upon gross changes in potassium balance or whether it may also occur in response to changes in plasma potassium concentration independently of changes in potassium balance.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies by Dluhy, Axelrod, Underwood, and Williams have shown that plasma aldosterone concentration can be increased acutely by intravenous potassium administration regardless of the previous dietary potassium intake (7). Similarly, aldosterone secretion by the isolated adrenals of dogs (3) and sheep (8) PRA in preinfusion blood samples were determined by a modification of the radioimmunoassay described by Haber, Koerner, Page, Kliman, and Purnode (11). Plasma aldosterone concentration was determined by a modification of the radioimmunoassay described by Bayard, Beitins, Kowarski, and Migeon (12) utilizing ammonium sulfate precipitation of bound antigen in the assay as described by Mayes, Furuyama, Kem, and Nugent (13).…”
Section: Introductionmentioning
confidence: 99%
“…From the Department of Medicine, Columbia University, College of Physicians and Surgeons and the Presbyterian Hospital in the City of New York, New York 10032 A B S T R A C T The effect of potassium administration and of dietary potassium deprivation on plasma renin activity and aldosterone excretion has been studied in 10 normal subjects and in 12 hypertensive patients maintained on a constant dietary regimen.…”
mentioning
confidence: 99%
“…Potassium administration and changes in potassium balance also exert a potent influence on aldosterone secretion (8)(9)(10)(11)(12)(13). Perfusion studies in animals have indicated that changes in plasma K+ act directly on the adrenal cortex to increase aldosterone secretion (11).…”
mentioning
confidence: 99%